Patient- and parent proxy-reported outcome measures for life participation in children with chronic kidney disease: a systematic review - Kerklaan, Jasmijn; Hannan, Elyssa; Baumgart, Amanda; Manera, Karine E; Ju, Angela; McCulloch, Mignon; Admani, Bashir; Dominello, Amanda; Esezobor, Christopher; Foster, Bethany; Hamilton, Alexander; Jankauskiene, Augustina; et al. (Nephrology, dialysis, transplantation, 2020)
The burden of chronic kidney disease (CKD) and its treatment may severely limit the ability of children with CKD to do daily tasks and participate in family, school, sporting and recreational activities. Life participation is critically important to affected children and their families; however, the appropriateness and validity of available measures used to assess this outcome are uncertain. The aim of this study was to identify the characteristics, content and psychometric properties of existing measures for life participation used in children with CKD.We searched MEDLINE, Embase, PsychINFO, Cumulative Index to Nursing and Allied Health Literature and the Cochrane Kidney and Transplant register to August 2019 for all studies that used a measure to report life participation in children with CKD. For each measure, we extracted and analyzed the characteristics, dimensions of life participation and psychometric properties.From 128 studies, we identified 63 different measures used to assess life participation in children with CKD. Twenty-five (40%) of the measures were patient reported, 7 (11%) were parent proxy reported and 31 (49%) had both self and parent proxy reports available. Twenty-two were used in one study only. The Pediatric Quality of Life Inventory version 4.0 generic module was used most frequently in 62 (48%) studies. Seven (11%) were designed to assess ability to participate in life, with 56 (89%) designed to assess other constructs (e.g. quality of life) with a subscale or selected questions on life participation. Across all measures, the three most frequent activities specified were social activities with friends and/or family, leisure activities and self-care activities. Validation data in the pediatric CKD population were available for only 19 (30%) measures.Life participation is inconsistently measured in children with CKD and the measures used vary in their characteristics, content and validity. Validation data supporting these measures in this population are often incomplete and are sparse. A meaningful and validated measure for life participation in children with CKD is needed.